(untitled) (BIBECHANA, 2010)
The binary mixtures of cabontetrachloride with isobutylmethylketone and benzaldehyde were studied at 308.15 by measuring viscosities and densities. The derived and excess viscosities, activation energy of flow and Grunberg-Nissan parameters have been calculated. It was found that these parameters are satisfactorily used to predict the strength and nature of molecular interactions. It was found that the strength of interactions in the systems studied is in the following order: CCl4 + IBMK>CCl4 + BD Keywords: Binary liquid; benzaldehyde; carbontetrachloride DOI: 10.3126/bibechana.v6i0.3932 BIBECHANA Vol. 6, March 2010 pp.9-14